EFFORTS TO IMPROVE DENTAL AND ORAL HEALTH KNOWLEDGE IN THE ELDERLY AT UPTD GRIYA WERDHA JAMBANGAN SURABAYA - Pinasti, Restika Anindya; Fauziah, Yessy Andriani; Fauzia, Bunga; Holanda, Ghita Hadi; Maharani, Aulia Dwi; Lelyana, Nora; Parisihni, Kristanti; Revianti, Syamsulina; Brahmanta, Arya (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2022)
The aging process is a process of slowly disappearing the ability of tissues to repair themselves or replace and maintain their normal functions. Tooth decay, tooth mobility, caries, halitosis, gingivitis, gingival recession, loss of periodontal attachment, and alveolar bone are changes in periodontal tissue that are commonly found in the elderly. If this is not treated, it can cause mobility and loss of teeth which will interfere with the function and activity of the oral cavity and will have an impact on the quality of life. Dental and oral health problems become one of the problems that have negative implications for overall health that in the end, it affects the quality of life in the elderly. Based on this analysis, in implementing the Tridarma of Higher Education, especially community service, the strategy is to increase public access to dental health services. One form of community service that can be carried out is promotive and preventive efforts. This activity is an educational approach to increase the ability and participation of the elderly community in maintaining dental health which can affect a person's quality of life.